SETTINGS OF TEMPERATURE AND TIME SAVING ON SEED GERMINATION OF Magnolia champaca (L.) Baill. ex Pierre - Nuradinda, Odetta Maudy; Estuningsih, Sri Pertiwi; Harmida, Harmida (BIOVALENTIA: Biological Research Journal, 2018)
Setting storage space temperature and time saving becomes an important application in supporting the development of plantations to provide seeds as needed and sustainable. The purpose of this research is to delay the rapid of seed germination in Magnolia champaca by assessing the effect of various suspend temperatures and times saving on seed germination of Magnolia camphaca . The research was conducted in Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University in February until June 2016. The method was used completely randomized design pattern Factorial by 3 factors with 12 treatments and 3 replications with the temperature: temperature ± 31°C, temperature ± 25 °C, temperature ± 18 °C, temperature ± 4 °C and the retention of time 0 week, 2 weeks , 4 weeks and 6 weeks. The parameters include the observation of germination rate, germination, vigor index and sprout morphology. The results of the research the treatment of interaction of temperature and time saving significantly affected on germination rate, germination and seed vigor index of Magnolia champaca. Germination speed, germination and vigor index were both produced by the treatment of storage at a temperature of ± 18 °C and a temperature of ± 25 °C at all times to keep (2 weeks, 4 weeks, 6 weeks) compared to control treatment. A normal sprout produced in temperature treatment ± 18 °C and ± 25 °C temperature ranges between 90-93%. An abnormal sprout produced in control treatment (0 week) by 25%. Measurement of moisture content and physiological maturity level of Magnolia champaca seed needs to be done before it is stored and germinated to test the viability of seeds of sprouts.